2022
DOI: 10.5114/aoms/150321
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge and long-term follow-up after an acute coronary syndrome: International Collaborative Group of CNCF position paper.

Abstract: IntroductionLong-term follow-up after an acute coronary syndrome (ACS) presents a crucial challenge due to the high residual cardiovascular risk and the potential for major bleeding events. Although several treatment strategies are available, this article focuses on patients who have undergone percutaneous coronary intervention (PCI) for ACS, which represent a frequent clinical situation. This position paper aims to support physicians in daily practice to improve the management of ACS patients.Material and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…The first is obviously associated with too few patients being treated with combination therapyand in particular, insufficient use of upfront combination LLT. This is despite our International Lipid Expert Panel (ILEP) recommendations on upfront combination therapy, which were published in April 2021 14 , and the reiteration of the advice in the European Atherosclerosis Society (EAS) Task Force paper 18 as well as an expert opinion paper published in EHJ 19 , and at least several national guidelines in which this approach was approved (e.g., in Poland, Spain, France) 7,[20][21][22] . Another reason for limited goal achievement is related to the fact that when non-statin drug(s) are added to statin therapy, the statin dose is reduced at the same time in many patients, and/or ezetimibe is discontinued in case of triple therapy with a PCSK9 targeted therapy approach.…”
mentioning
confidence: 99%
“…The first is obviously associated with too few patients being treated with combination therapyand in particular, insufficient use of upfront combination LLT. This is despite our International Lipid Expert Panel (ILEP) recommendations on upfront combination therapy, which were published in April 2021 14 , and the reiteration of the advice in the European Atherosclerosis Society (EAS) Task Force paper 18 as well as an expert opinion paper published in EHJ 19 , and at least several national guidelines in which this approach was approved (e.g., in Poland, Spain, France) 7,[20][21][22] . Another reason for limited goal achievement is related to the fact that when non-statin drug(s) are added to statin therapy, the statin dose is reduced at the same time in many patients, and/or ezetimibe is discontinued in case of triple therapy with a PCSK9 targeted therapy approach.…”
mentioning
confidence: 99%
“…A major difference in this study compared to the other was that cardiac rehabilitation nurses were responsible for optimizing lipid-lowering therapy in patients who had not achieved target LDL-C levels [ 3 , 7 ]. A Danish population-based study based on 4377 patients with a mean age of 67.8 ± 13.6 showed that 89.4% of patients had LDL-C > 1.8 mmol/L at the time of ACS [ 9 - 11 ]. In comparison to other European countries, patients with ACS in Austria are generally followed up in the community for lipid-lowering therapy optimization and only patients with severely reduced left ventricular ejection fraction are followed up in a hospital setting [ 3 , 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Antithrombotic therapy has been for years the mainstay to prevent disease relapses, but nowadays several other drugs have proven to be effective in decreasing overall cardiovascular risk and major adverse cardiovascular events, even after an acute coronary syndrome. 3 Prevention of heart failure (HF) with prompt revascularization when amenable and aggressively tackling risk factors have been shown to be particularly effective, given the detrimental interplay among these clinical entities. 4 Intriguingly, metabolic derangements in myocardiocytes stem from an imbalance in myocardial energy consumption and reduced oxygen supply, because of decreased blood flow in CAD, resulting in myocardial ischemia.…”
mentioning
confidence: 99%
“…Antithrombotic therapy has been for years the mainstay to prevent disease relapses, but nowadays several other drugs have proven to be effective in decreasing overall cardiovascular risk and major adverse cardiovascular events, even after an acute coronary syndrome. 3…”
mentioning
confidence: 99%